Practical Fiqh Education: Guidance on Proper Ablution Procedures According to the Sunnah for Students of SMPN 35 Medan - Marhan Hasibuan; Muhammad Arif Hidayat (Yayasan Rahmat Islamiyah, 2026)
This community service activity aims to improve students’ understanding and practical skills in performing ablution (wudhu) according to the Sunnah through a practical fiqh education approach. The background of this program is based on the existing gap between students’ theoretical knowledge and their actual practice of worship, particularly in performing ablution, which is a prerequisite for valid prayer. The activity was conducted at SMP Negeri 35 Medan, involving approximately 35 students as participants. The method employed an educative-participatory approach, including interactive lectures, demonstrations, simulations, hands-on practice, and intensive mentoring. The results indicate a significant improvement in students’ cognitive, affective, and psychomotor domains. The average score of students’ understanding increased from a moderate level in the pre-test to a high level in the post-test. Furthermore, approximately 85% of the students were able to correctly perform ablution according to the Sunnah after participating in the program. In terms of affective outcomes, students showed increased awareness and motivation to improve the quality of their worship practices. This activity also demonstrates that applicative and participatory learning methods are more effective than conventional approaches in teaching fiqh. Therefore, this practical fiqh education program can serve as an innovative learning model to enhance the quality of religious education in schools. Future efforts should focus on integrating similar programs into regular school activities to ensure sustainable impact.